Effects of time pressure on conflict resolution performance using conflict resolution aid in future air traffic control - Ow, Diana Ying Zhi (2015)
Air traffic is expected to rise rapidly in the next few years globally and especially in Asia and current Air Traffic Management will not be able to handle the increased traffic capacity. Economical, innovative and efficient solutions in Air Traffic Control are needed to resolve this problem to prevent traffic congestions and reduce fuel consumption. At present, there is a lack of research on automated conflict resolution aid (CRA) reliability and impact of time pressure on Air Traffic Controllers (ATCOs). The objective of this report is to investigate the effect secondary conflicts and consequential time pressure levels have on ATCOs’ performance. Twelve participants participated in this study. Four sessions were required of the participants, the first being a training session and the other sessions corresponding to the testing conditions of reliable CRA, unreliable CRA with high time pressure and unreliable CRA with low time pressure. The performance is analyzed in terms of Percentage of Resolve Conflict, Conflict Resolution Time and Number of Error Count. Situational Awareness of the participants was measured using Situation Present Assessment Method (SPAM). The results of this study indicate that an unreliable CRA results in poorer ATCO performance and low SA, with high time pressure level producing the worst results. The secondary conflict look-ahead time difference between the two unreliable conditions had a significant impact on ATCOs.